Rozwój i główne nurty w badaniach efektywności szkoły - Nowosad, Inetta (Studia Edukacyjne, 2020)
This article isolates the main phases of the research into school effectiveness, at the same time emphasizing the specificityof attitudes, the dominant directions and the conclusions drawn in particular phases. The approach adopted emphasizes key achievements which have influencedthe direction of research and as such define the contemporary understanding of an effective school.